Infertility in the male - Lipshultz, Larry I., 1942-; Howards, Stuart S., 1937-; Niederberger, Craig S. (Cambridge : Cambridge University Press, 2009)
The new edition of this canonical text on male reproductive medicine will cement the book's market-leading position. Practitioners across many specialties - including urologists, gynecologists, reproductive endocrinologists, medical endocrinologists and many in internal medicine and family practice - will see men with suboptimal fertility and reproductive problems. The book provides an excellent source of timely, well-considered information for those training in this young and rapidly evolving field. While several recent books provide targeted 'cookbooks' for those in a male reproductive laboratory, or quick reference for practising generalists, the modern, comprehensive reference providing both a background for male reproductive medicine as well as clinical practice information based on that foundation has been lacking until now. The book has been extensively revised with a particular focus on modern molecular medicine. Appropriate therapeutic interventions are highlighted throughout.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Infertility, Male